2017
DOI: 10.1007/978-1-4939-6854-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli-Based Expression and In Vitro Activity Assay of 1-Aminocyclopropane-1-Carboxylate (ACC) Synthase and ACC Oxidase

Abstract: 1-Aminocyclopropane-1-carboxylate (ACC) synthase and ACC oxidase are key enzymes in the ethylene biosynthetic pathway in plant tissues, and in vitro assay of their activities is indispensable for analysis, especially, for studying the action mechanism of inhibitors of ethylene biosynthesis. The enzymes can be obtained from plant tissues that are producing ethylene abundantly, such as ripening fruit- and senescing flower tissues, but it is necessary to separate the enzymes from co-extracted ACC by partial purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Expression analysis revealed that ACOs show a high tissue specificity, with LeACO1 and LeACO2 expressed in guard cells ( Spanu et al, 1991 ). Many reports show that the silencing of ACO genes or the inhibition ACO activity reduces ethylene content in plant cells ( Chao et al, 2013 ; Satoh and Kosugi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expression analysis revealed that ACOs show a high tissue specificity, with LeACO1 and LeACO2 expressed in guard cells ( Spanu et al, 1991 ). Many reports show that the silencing of ACO genes or the inhibition ACO activity reduces ethylene content in plant cells ( Chao et al, 2013 ; Satoh and Kosugi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the role of ethylene as an enhancer of fruit respiration [ 47 ], controlling its production might be essential to ensure the storage quality of fruits [ 48 , 49 ]. In previous studies, a controlled atmosphere has been widely used in postharvest preservation, showing reduced ethylene accumulation [ 50 , 51 ] by blocking its biosynthesis and absorption ( Figure 6 ) [ 52 , 53 , 54 ]. This explained the lower respiration rate for chestnuts in treated groups ( Figure 1 C), relative to CT.…”
Section: Discussionmentioning
confidence: 99%
“…For the construction of an expression plasmid, the entire coding region was amplified from DcACO1 cDNA [20] by PCR. DcACO1 protein was expressed from DcACO1 cDNA in E. coli cells as described elsewhere [21]. ACC oxidase activity was assayed by the standard method [21].…”
Section: Search For a Possible Biochemical Action Mechanism Of Pdca Amentioning
confidence: 99%
“…DcACO1 protein was expressed from DcACO1 cDNA in E. coli cells as described elsewhere [21]. ACC oxidase activity was assayed by the standard method [21]. The recombinant ACC oxidase had a Km of 118 mM for ACC.…”
Section: Search For a Possible Biochemical Action Mechanism Of Pdca Amentioning
confidence: 99%